CT radiomics associations with genotype and stromal content in pancreatic ductal adenocarcinoma - Attiyeh, Marc A.; Chakraborty, Jayasree; McIntyre, Caitlin A.; Kappagantula, Rajya; Chou, Yuting; Askan, Gokce; Seier, Kenneth; Gonen, Mithat; Basturk, Olca; Balachandran, Vinod P.; Kingham, T. Peter; D’Angelica, Michael I.; et al. (Abdominal imaging, 2019)
Purpose The aim of this study was to investigate the relationship between CT imaging phenotypes and genetic and biological characteristics in pancreatic ductal adenocarcinoma (PDAC). Methods In this retrospective study, consecutive patients between April 2015 and June 2016 who underwent PDAC resection were included if previously consented to a targeted sequencing protocol. Mutation status of known PDAC driver genes ( KRAS , TP53 , CDKN2A , and SMAD4 ) in the primary tumor was determined by targeted DNA sequencing and results were validated by immunohistochemistry (IHC). Radiomic features of the tumor were extracted from the preoperative CT scan and used to predict genotype and stromal content. Results The cohort for analysis consisted of 35 patients. Genomic and IHC analysis revealed alterations in KRAS in 34 (97%) patients, and changes in expression of CDKN2A in 29 (83%), SMAD4 in 16 (46%), and in TP53 in 29 (83%) patients. Models created from radiomic features demonstrated associations with SMAD4 status and the number of genes altered. The number of genes altered was the only significant predictor of overall survival ( p = 0.016). By linear regression analysis, a prediction model for stromal content achieved an R 2 value of 0.731 with a root mean square error of 19.5. Conclusions In this study, we demonstrate that in PDAC SMAD4 status and tumor stromal content can be predicted using radiomic analysis of preoperative CT imaging. These data show an association between resectable PDAC imaging features and underlying tumor biology and their potential for future precision medicine.